De la dictadura a la democracia : Manuel Fraga Iribarne - Anderle, Ádám (Acta Hispanica, 2008)
The essay examines the political career of the renowned Spanish conservative politician. As a young jurist, Fraga Iribarne quickly developed an academic, diplomatic and political career in the Spanish Franco regime after the Second World War; he even occupied the—rather infamous—post of the Minister of Interior. Still, Fraga Iribarne was one of the few Francoist statesmen who recognized the importance of a democratic transition, and he became one of the key figures of the Spanish transition after the death of Franco. He also participated intensely in the creation of the democratic constitution of 1978, founded and presided People’s Alliance (Alianza Popular), a party of conservative orientation, and was the President of Galicia’s Xunta for 15 years. The author emphasizes the key role of Fraga Iribarne in the democratic transition, pointing out that it was him who, in the autumn of 1976, introduced the Communist leader Santiago Carrillo to the members of the Francoist elite club, Club 21st Century, causing a great stir in the Madrid élite. Fraga’s move was a clear statement that in democratic pluralistic party politics, communist and other leftist elements also have the right to be represented. Still, the documents of the era also point out that Juan Carlos, the young monarch, also had a decisive role in the positive reception of democratic ideas by the Francoist élite.